The effects of government ownership on bank lending - Sapienza, Paola (Journal of Financial Economics, 2004)
This paper uses information on individual loan contracts to study the effects of government ownership on bank lending behavior. State-owned banks charge lower interest rates than do privately owned banks to similar or identical firms, even if firms are able to borrow more from privately owned banks. State-owned banks mostly favor large firms and firms located in depressed areas. The lending behavior of state-owned banks is affected by the electoral results of the party affiliated with the bank: the stronger the political party in the area where the firm is borrowing, the lower the interest rates charged.